Analysis On Genetic Distance Of The German Cockroach, Blattella Germanica From Different Localities By Using Microsatellites Technique - Norsaliatie, Hassan (Universiti Malaysia Sarawak (UNIMAS), 2014)
The German cock.roaches are the most common pest in hotels, restaurants and urban apartment in major urban cities in Malaysia. This study aimed to characterize allelic variations of B. germanica from different localities using microsatellite DNA marker and to determine the genetic distance of B. germanica from different localities which are from Malaysia, Singapore, Indonesia and Thailand. A total of 102 individuals were collected and extracted with phenol-chloroform method and amplified with five microsatellite loci developed by Booth et al., (1997). Based on the analysis of molecular variance (AMOV A), the global F sT value among all population is 0.260. Analysis of the pairwise FsT value and neighbour joining (NJ) tree show that population of Ayer Itam, Penang; Melia Kuala Lumpur and Cavenough Road; Bukit Timah Road show expected results as they were from the same nation and having low value in the genetic distance. This indicates that the populations are relatively related and share recent common ancestor with subsequent differentiation due to aggregation behavior. It can be deduced that the passive dispersal through human-mediated dispersal through human migration and transportation is an important role in B. germanica distribution among all eleven population.